Cardiac remodeling and renin-angiotensin system - González, Germán E. (2009)
Myocardial infarction (MI) leads to structural alterations involving the infarcted as well as the non-infarcted areas in a process known as ventricular remodeling. The early phase of remodeling, which starts at the beginning of the MI, is associated with geometric changes and dilation of the infarct zone, as a process collectively known as expansion of the scar. Subsequently, this dilation may progress to the whole ventricle and it is associated with myocytes hypertrophy and fibrosis in the remote zones. These structural changes start on during the initial phase of the healing process of the infarction, contribute to ventricular dysfunction, cause a progression to heart failure and increase mortality. The systemic and cardiac renin-angiotensin systems (RAS) are stimulated post-MI and actively participate in ventricular remodeling, favoring the healing process of the infarct area as well as myocytes hypertrophy, fibrosis, and most of the events associated to the remodeling of non-MI zones. In this review, we analyze different general aspects of postmyocardial infarct ventricular remodeling and the activation and participation of the renin- angiotensin system in its evolution.